UNRAVELING THE PATHOPHYSIOLOGY OF ORAL SUB MUCOUS FIBROSIS: MECHANISMS AND INSIGHTS - Dr. Salman Siddeeqh, Dr. Nupur Hingad, Dr. Arun Gopinathan Pillai, Dr. Vidyullatha B. Gopalakrishna, Dr. Manju Roby Philip, Dr. Ali Aboalela (South Eastern European Journal of Public Health, 2025)
Oral Submucous Fibrosis (OSF) is defined by enhancing irreversible fibrosis of the oral mucous membrane, a potentially malignant disorder that results in dysphagia, restricted mouth opening and in an advanced case, the onset of malignancy. Immunological, environmental, and genetic factors all play a part in the complex pathophysiology of OSF . The most well-established risk factor is long-term chewing of areca nuts (betel nuts), which causes an inflammatory response that produces collagen and other extracellular matrix components, ultimately resulting in fibrosis. The pro-inflammatory cytokines such as TNF-α, IL-1 and TGF-β influences the activation of fibroblast and collagen deposition, may be involved, according to molecular research. The disease also progresses as a result of oxidative stress and genetic abnormalities, especially in genes linked to collagen. In a small percentage of cases, this diseased process may eventually result in malignant transformation. The pathophysiology of OSF is reviewed in this paper, with an emphasis on molecular pathways along with prospective therapeutic targets for treatment and prevention.